2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037533
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale dispersion entropy for the regional analysis of resting-state magnetoencephalogram complexity in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a progressive and irreversible brain disorder of the nervous system affecting memory, thinking, and emotion. It is the most important cause of dementia and an influential social problem in all the world. The complexity of brain recordings has been successfully used to help to characterize AD. We have recently introduced multiscale dispersion entropy (MDE) as a very fast and powerful tool to quantify the complexity of signals. The aim of this study is to assess the ability of MDE, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Gómez et al [ 112 ] reported MSE profiles that represented the SampEn values of each coarse-grained time series relative to the scale factor. Azami et al [ 113 ] found that the values of multiscale dispersion entropy (MDE), multiscale permutation entropy (MPE), and MSE in AD patients were lower than those in NCs at short scale factors, while at long scale factors, the MDE and MSE values from AD subject signals had higher values [ 112 ]. In contrast, the MPE values at long scale factors were very similar for AD patients and NCs.…”
Section: Resultsmentioning
confidence: 99%
“…Gómez et al [ 112 ] reported MSE profiles that represented the SampEn values of each coarse-grained time series relative to the scale factor. Azami et al [ 113 ] found that the values of multiscale dispersion entropy (MDE), multiscale permutation entropy (MPE), and MSE in AD patients were lower than those in NCs at short scale factors, while at long scale factors, the MDE and MSE values from AD subject signals had higher values [ 112 ]. In contrast, the MPE values at long scale factors were very similar for AD patients and NCs.…”
Section: Resultsmentioning
confidence: 99%
“…However, mvMSE and mvMFE have the following shortcomings: (1) mvMSE and mvMFE values may be unreliable and unstable for short signals (300 sample points); (2) they are not quick enough for real-time applications; and (3) computation of mvMSE and mvMFE of a signal with a large number of channels needs to have large memory space, as shown later. To address these drawbacks and due to the advantages of multiscale dispersion entropy (DispEn-MDE) over the state-over-the-art multiscale entropy techniques in terms of distinguishing different kinds of dynamics of univariate synthetic and real time series and computation time [ 27 , 28 , 29 ], we propose four algorithms to extend our recently developed MDE to its multivariate forms, termed multivariate MDE (mvMDE). To evaluate the mvMDE methods, we use both synthetic and real multivariate datasets.…”
Section: Introductionmentioning
confidence: 99%
“…. When dealing with the fault of the bearing vibration signal, it is often difficult to know the most suitable time scales, and signal nonstationarity and irregularity tend to be very strong; in order to solve this problem well, Azami et al proposed multiscale discrete entropy (MDE) in 2017 [47] and proved that the MDE approach based on processing of the nonstationary signal has a strong ability of feature extraction. e flow of MDE is shown in Figure 3.…”
Section: Multiscale Dispersion Entropy (Mde)mentioning
confidence: 99%
“…Moreover, bearing fault diagnosis based on multiscale entropy has been widely used in the field of intelligent fault, such as multiscale fuzzy entropy (MFE) [44] and multiscale permutation entropy (MPE) [45]. Rostaghi and Azami have proposed dispersion entropy (DE) [46] and multiscale dispersion entropy (MDE) [47]. MDE does not need to sort the amplitude of each embedded vector nor does it need to calculate the distance between any two compound delay vectors with embedded dimensions m and m + 1, which makes DE and MDE faster than PerEn, PerEn, and MperEn, significantly.…”
Section: Introductionmentioning
confidence: 99%